The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1038/s41398-021-01707-x
|View full text |Cite
|
Sign up to set email alerts
|

Trauma and posttraumatic stress disorder modulate polygenic predictors of hippocampal and amygdala volume

Abstract: The volume of subcortical structures represents a reliable, quantitative, and objective phenotype that captures genetic effects, environmental effects such as trauma, and disease effects such as posttraumatic stress disorder (PTSD). Trauma and PTSD represent potent exposures that may interact with genetic markers to influence brain structure and function. Genetic variants, associated with subcortical volumes in two large normative discovery samples, were used to compute polygenic scores (PGS) for the volume of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 73 publications
0
5
0
Order By: Relevance
“…Indeed, while speculative, it is possible that the associations observed between hippocampal functional connectivity and hippocampal volume in the present study reflect the influence of stress exposure. For example, the robust relations observed between the hippocampus and IPL in this study may be related to the IPL’s sensitivity to adverse environmental influence, similar to the hippocampus (e.g., Davis et al, 2017; Merz et al, 2019; Zheng et al, 2021). Research has found inverse associations between allostatic load (i.e., a quantified index of multiple stress indicators) and IPL thickness in both healthy individuals and those with schizophrenia (Chiappelli et al, 2017).…”
Section: Discussionmentioning
confidence: 77%
“…Indeed, while speculative, it is possible that the associations observed between hippocampal functional connectivity and hippocampal volume in the present study reflect the influence of stress exposure. For example, the robust relations observed between the hippocampus and IPL in this study may be related to the IPL’s sensitivity to adverse environmental influence, similar to the hippocampus (e.g., Davis et al, 2017; Merz et al, 2019; Zheng et al, 2021). Research has found inverse associations between allostatic load (i.e., a quantified index of multiple stress indicators) and IPL thickness in both healthy individuals and those with schizophrenia (Chiappelli et al, 2017).…”
Section: Discussionmentioning
confidence: 77%
“…To determine the maximizing P value threshold from each meta-GWAS, we generated 1001 PRSs in OMG-SCD and Walk-PHaSST with thresholds ranging from P = .0001 to P = 1, in increments of .001, as described previously. 44 Each PRS was then tested for association with proteinuria and eGFR using logistic and linear regression, respectively, in each cohort (R glm ), followed by a fixed-effects meta-analysis in R metafor . 45 A Bonferroni correction was applied to account for the 1001 thresholds examined ( P = 5 × 10 –5 ).…”
Section: Methodsmentioning
confidence: 99%
“…In either event, there is an inverse relationship between subregion volumes and PTSD severity (Ben-Zion et al 2022: 666–7; cf. Zheng et al 2021, 7–8). Smaller volumes correspond with more severe progressions, suggesting that disruption or reduction in the functions of these areas underwrites PTSD symptoms (Woon & Hedges 2009; Yehuda 2002, 110).…”
Section: Post-traumatic Stress Disordermentioning
confidence: 99%
“…Measurable changes in the brain ‘signify an indelible sensory imprint of a maladaptively processed experience’ which impairs cognitive and emotional capacities (Sherin & Nemeroff 2011, 274). Thereafter, symptoms reflect the roles of affected neurological substrates—there are causal relationships between the architecture of these brain areas and PTSD symptomatology (Zheng et al 2021, 7).…”
Section: Post-traumatic Stress Disordermentioning
confidence: 99%